2002
DOI: 10.1074/jbc.m207570200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-regulated Gene Expression inArabidopsis

Abstract: Regulated gene expression is an important mechanism for controlling cell cycle progression in yeast and mammals, and genes involved in cell division-related processes often show transcriptional regulation dependent on cell cycle position. Analysis of cell cycle processes in plants has been hampered by the lack of synchronizable cell suspensions for Arabidopsis, and few cell cycle-regulated genes are known. Using a recently described synchrony system, we have analyzed RNA from sequential samples of Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
172
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(186 citation statements)
references
References 94 publications
9
172
1
1
Order By: Relevance
“…Three MYB genes have peak expressions at the S phase, whereas five other MYB genes are mainly expressed at the M phase [28,29]. Two other MYB genes are expressed at the G1 and G2 phases [29].…”
Section: Discussionmentioning
confidence: 99%
“…Three MYB genes have peak expressions at the S phase, whereas five other MYB genes are mainly expressed at the M phase [28,29]. Two other MYB genes are expressed at the G1 and G2 phases [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ectopic expression of CYCD3;1, whose expression and activity are also normally activated in late G 1 phase (8,12,31), specifically promotes the mitotic cell cycle, leading to increased cell number, reduced cell size, and reduced endocycling (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that cyclin-induced activation of NtmybA2 requires many putative sites of phosphorylation and that each site makes a contribution to the cyclininduced activation. At least two regions of NtmybA2 are important for cyclin-mediated regulation; one is located in the conserved domain that includes motifs 6 -10, and the other, including motifs [11][12][13][14][15][16][17][18][19][20], is located at the carboxyl terminus.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, a wide range of G 2 /M phasespecific genes seem to be regulated by 3Rmyb proteins. A recent analysis of the Arabidopsis transcriptome, using a DNA tip, revealed that 93 of 8,250 genes tested showed G 2 /M phasespecific expression, with kinetics of expression similar to those of cyclin B genes (18). Among these 93 genes, ϳ20% include MSA consensus sequence YCYAACGGYY (where Y indicates C or T) in the promoter region, defined as the 1-kb region upstream of the site of initiation of translation.…”
mentioning
confidence: 99%